2009
DOI: 10.1116/1.3137967
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural compositional, and optical characterization of GaN grown by metal organic vapor phase epitaxy on ZnO epilayers

Abstract: Residual and intentional n-type doping of ZnO thin films grown by metal-organic vapor phase epitaxy on sapphire and ZnO substrates

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Figure 5 shows the SIMS concentration profiles for Ga, In, N and Zn along the growth direction (in a sample with a thicker ZnO layer than that shown in Figure 1). The profile for Zn indicates some diffusion of Zn into the InGaN/GaN near the GaN/ZnO interface [8][9]. The simulation suggested that an incident electron beam, with an energy of 5kV, stimulated a response from most of the InGaN/GaN layer depth.…”
Section: Ingan Znomentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 5 shows the SIMS concentration profiles for Ga, In, N and Zn along the growth direction (in a sample with a thicker ZnO layer than that shown in Figure 1). The profile for Zn indicates some diffusion of Zn into the InGaN/GaN near the GaN/ZnO interface [8][9]. The simulation suggested that an incident electron beam, with an energy of 5kV, stimulated a response from most of the InGaN/GaN layer depth.…”
Section: Ingan Znomentioning
confidence: 99%
“…GaN has the advantage, however, of a mature know-how for p-type doping, while ZnO has proven to be more crystallographically compliant to non-native substrates than GaN. With a view to exploiting both of these strong points, ZnO layers have been proposed as buffer layers for the regrowth of GaN-based p-n devices on amorphous and mismatched substrates [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…X-ray diffraction (XRD) measurements revealed epitaxial growth [8,9] with a FWHM of 0.006° for the (0002) peak high resolution omega scan and an (open-detector) omega rocking curve value of about 0.05°, characteristic of a highly oriented material with very low crystallographic dispersion. The 2θ-ω scan of the (0002) peak gave a c lattice parameter of 5.215 Å.…”
mentioning
confidence: 99%